Influence Electronic Word Of Mouth (E-Wom) To Purchase Intention Wardah Cosmetic Products With Brand Image As A Mediation Variable - Kurniawan, Erwin Putra Ragil Wahyu; Marsudi; Aziz, Noor (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The usage of electronic word of mouth in consumer communications today helped the emergence of purchase intention on certain products, especially in the field of cosmetics for women, brand image of existing products also helps increase consumer purchasing intentions. This research aims to find out whether electronic word of mouth has a significant effect on purchase intention for Wardah cosmetic products with brand image as a mediating variable using techniques of structural equation modeling with the help of analytical tools Smart PLS 4. The type of research used is quantitative research with a sample size of 120 respondents who meet the sample criteria and were taken using techniques of accidental sampling. This research data was obtained through a questionnaire in the form of google form which was distributed to students at the University of Muhammadiyah Malang. The research results show that electronic word of mouth positive and significant effect on purchase intention, electronic word of mouth positive and significant effect on brand image, brand image significant effect on purchase intention, and electronic word of mouth positive influence on purchase intention through brand image as a mediating variable.